Socio-Economic Impact of the Mass Rapid Transit (MRT) System in Dhaka: A Case Study of Mirpur Stations - Raj, Shahriar Iqbal; Mohino, Inmaculada; Khatun, Farjana (Journal of Contemporary Urban Affairs, 2024)
Mass Rapid Transport (MRT) has become pivotal in sustainable urban transportation, especially in densely populated cities like Dhaka, the capital of Bangladesh. Dhaka is implementing its first MRT system, which includes 17 stations, with three located in Mirpur. Mirpur, a significant area due to its diverse economic activity and population, is an important case study for understanding the effects of the MRT system. The study area spans 58.66 square kilometers and has a population of 632,664, representing a zone with unplanned mixed uses and a spontaneously developed favorable job-housing ratio conducive to transit-oriented development (TOD). Challenges such as last-mile connectivity and capacity limitations could impede the MRT's socio-economic potential. Moreover, the current land use and urban planning framework are not adequately prepared to support future TOD. This research highlights the necessity of proactive legislative changes and infrastructural improvements to optimize the success of Mirpur's MRT stations. Despite being in service for only a year and facing a lack of real-life data, this study focuses on Mirpur MRT stations to explore the socio-economic impacts of MRT systems, aiming to enhance knowledge in urban transportation and development.